Unilateral segmental odontomaxillary dysplasia: A rare entity of 3 cases and review - Shalu Rai; Rohit Malik; Sapna Panjwani; Deepankar Misra; Sankalp Verma (Wolters Kluwer Medknow Publications, 2014)
Segmental odontomaxillary dysplasia (SOD) is an uncommon, nonhereditary, rare developmental disorder primarily involving the posterior part of the maxilla and related dental components. It is a rare condition of uncertain etiology that results in painless unilateral expansion of the posterior dentoalveolar complex, gingival hyperplasia, lack of one or both premolars in the affected area, delayed eruption of adjacent teeth and malformations of the primary molars. Radiographically, the affected bone is thickened and irregular in outline, with a coarse trabecular pattern that is vertically oriented resulting in a relatively radioopaque granular appearance. The treatment is focused on extraction of the involved teeth, while in some milder cases the teeth may be retained for a long period. The treatment plan should be based on the degree of involvement as well as the functional and esthetic needs in each case. Considering the rarity of the condition, we report three cases of SOD with variable presentations in a 45-year-old, 24-year-old and 23-year-old individual.